2018
DOI: 10.1021/acs.jpca.8b09526
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Dynamics of Hydrogen-Bonded Cytosine Microsolvated Clusters with Protic and Aprotic Polar Solvents

Abstract: Microsolvation effects on the ultrafast excitedstate deactivation dynamics of cytosine (Cy) were studied in hydrogen-bonded Cy clusters with protic and aprotic solvents using mass-resolved femtosecond pump−probe ionization spectroscopy. Two protic solvents, water (H 2 O) and methanol (MeOH), and one aprotic solvent, tetrahydrofuran (THF), were investigated, and transients of Cy•(H 2 O) 1−6 , Cy•(MeOH) 1−3 , and Cy•THF microsolvated clusters produced in supersonic expansions were measured. With the aid of elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
(254 reference statements)
1
5
0
Order By: Relevance
“…[5] However, in the case of cytosine and its methylated analogue, hydrogen bonding with water, methanol, and tetrahydrofuran does not alter the excited state dynamics, significantly. [6] Similar results were also reported for adenine and its hydrogen-bonded complex with water. [7] In a nutshell, it has been suggested that the nature of coupling (or lack of it) of the initially excited 1 ππ* bright state to one or more low-lying excited states largely determines the nature of excited state dynamics.…”
Section: Introductionsupporting
confidence: 75%
“…[5] However, in the case of cytosine and its methylated analogue, hydrogen bonding with water, methanol, and tetrahydrofuran does not alter the excited state dynamics, significantly. [6] Similar results were also reported for adenine and its hydrogen-bonded complex with water. [7] In a nutshell, it has been suggested that the nature of coupling (or lack of it) of the initially excited 1 ππ* bright state to one or more low-lying excited states largely determines the nature of excited state dynamics.…”
Section: Introductionsupporting
confidence: 75%
“…Since the photophysics of nucleobases is strongly influenced by hydrogen bonding, it is important to compare the dynamics of aqueous nucleobases with those of isolated molecules in the gas phase. However, since nucleosides and nucleotides are vulnerable to evaporation at high temperatures, , we studied gaseous Thy and Ura alternatively. ,, Thy and Ura are known to have keto forms in the gas phase almost exclusively; the minute amount of keto-enol tautomers, which have higher energy than the keto form by more than 9 kcal/mol, is practically negligible. On the other hand, the dominant tautomer of gaseous cytosine (Cyt) has a noncanonical form so that Cyt was excluded in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Other rare tautomers have also been observed by various spectroscopic techniques. [5][6][7][8][9][10][11] Additionally,t he effect of water molecules on the structural dynamics and tautomerism of cytosine have been investigated, [12,13] showing that water can facilitate tautomerization from the canonical form to the rare tautomers by lowering the activation barriers of the prototropic process.T he high stability of the keto-amino tautomers in solution is derived from their large dipole moments. [3,14] Early thermodynamic and kinetic studies showed that the major KAN1H and minor KAN3H forms (Scheme S1 a) are in equilibrium in aqueous solution.…”
mentioning
confidence: 99%